Active/Passive, 'Diminished'/'Beautiful', 'Light' from Above and Below: Rereading Shekhinah's Sexual Desire in Zohar al Shir ha-Shirim (Song of Songs). (May 2020) - Devine, Luke
In Zohar al Shir ha-Shirim, the Zohar's reading of Song of Songs, Shekhinah, echoing themes associated with the Shulamite of the biblical text, consistently initiates cosmic union. Sexual desire in the zoharic texts is a form of capital necessary to facilitate sefirotic intercourse, although scholarly readings of the zoharic corpus often identify Shekhinah as a passive receptacle. This, however, is only true if the endemic contradictions within the texts are glossed over. In Song of Songs, the Shulamite's sexual 'initiative' is core. This was not lost on the author(s) of Zohar al Shir ha-Shirim, who, in struggling to explain Shekhinah's sefirotic role in line with the erotics of Song of Songs, inescapably echoed the 'depatriarchalizing' themes of the biblical text. As this article demonstrates, in Zohar al Shir ha-Shirim, Shekhinah is active and repeatedly encourages and frustrates cosmic sexual intercourse. Zohar al Shir ha-Shirim shows that it is possible to reread Shekhinah's role beyond the androcentrism of the authors as well as scholarly assumptions about her passivity.